Economic and Welfare Impacts of Indonesia's Tourism Sector - Arif Haryana (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2020)
This paper was aimed to see the impact of the development of tourism sector during the Indonesia’s Mid-Term Development Planning Period (RPJMN) 2015-2019. The analysis was also aimed to contribute to the Terminal Evaluation of RPJMN 2015-2019. The implementation of this impact evaluation analyzes the achievement of the basic target sector of tourism to the national economy and the welfare of individual workers and business units engaged in the field of tourism. The impact on the national economy is evaluated based on relevant secondary data. While the impact analysis on the welfare of inividual worker and tourism business unit, was carried out using primary data obtained through surveys. The field was conducted on June-July 2019 covering all provinces. There was 2.125 individual workers and 1.082 business unit participate as respondents. Proportional sampling method was used to determine the number of respondents in each province. The study found that during the 2014-2019, the competitiveness of the Indonesian tourism sector has increased and has encouraged the increasing number of foreign tourists visit. The sector has experienced growth and contributes positively to the national economy. At micro level, the sector generated positive impact on tourism business unit as most of them were claiming of gaining profit sustainably during that period. However, the impact was still limited in improving the ability of business units to innovate in product development and the ability to generate new employment. There were also very limited positive impact on the welfare of the sector’s workers. In term of the average earning per month, the welfare of workers in this sector is still relatively low compared to workers in all other sectors.